2022
DOI: 10.1101/2022.07.06.22277294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergency Department Quality of Care for Sickle Cell Disease in Ontario, Canada: A Population-Based Matched Cohort Study

Abstract: BackgroundAcute vaso-occlusive crisis (VOC) in sickle cell disease (SCD) often leads patients to seek emergency department (ED) care. The landscape of SCD ED care within Canada’s universal and publicly funded healthcare system remains largely undefined. Here, we sought to address this knowledge gap by characterizing the quality of SCD VOC ED and inpatient care in Ontario, Canada.MethodsWe used population-level health administrative data to identify patients with SCD in Ontario who presented to the ED with SCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Access to timely and quality emergency care and differences between pediatric and adult populations is becoming recognized as a concern in other provinces as well. In Ontario, one study found that adults are waiting much longer than their pediatric counterparts, despite visiting the ED 2.5 times more frequently (12). This highlights the importance of collaboration for SCA emergency management.…”
Section: Discussionmentioning
confidence: 99%
“…Access to timely and quality emergency care and differences between pediatric and adult populations is becoming recognized as a concern in other provinces as well. In Ontario, one study found that adults are waiting much longer than their pediatric counterparts, despite visiting the ED 2.5 times more frequently (12). This highlights the importance of collaboration for SCA emergency management.…”
Section: Discussionmentioning
confidence: 99%
“…Access to timely and quality emergency care and differences between pediatric and adult populations are becoming recognized as a concern in other provinces as well. In Ontario, one study found that adults are waiting much longer than their pediatric counterparts, despite visiting the ED 2.5 times more frequently [15]. This highlights the importance of collaboration for SCA emergency management.…”
Section: Discussionmentioning
confidence: 99%
“…Prevailing laws during the study mandated medical reporting of all patients with a gun injury . Emergency care was universally available, publicly funded by the Ontario Health Insurance Plan (OHIP), and tracked through encrypted linked records after a lag for data security and collection . Patient-level linked health services data were available to qualified researchers through population-based electronic medical records at the Institute for Clinical Evaluative Sciences (ICES) …”
Section: Methodsmentioning
confidence: 99%